The Study of Short-Term Plastic Visual Perceptual Training Based on Virtual and Augmented Reality Technology in Amblyopia - Fan Tan; Xubo Yang; Yuchen Fan; Yongchuan Liao (Journal of Ophthalmology)
Backgrounds. The treatment for amblyopia can have a substantial impact on quality of life. Conventional treatments for amblyopia have some limitations, then we try to explore a new and effective method to treat amblyopia. This study aimed to determine the potential effect of short-term plastic visual perceptual training based on VR and AR platforms in amblyopic patients. Methods. All observers were blinded to patient groupings. A total of 145 amblyopic children were randomly assigned into 2 groups: VR group (71 patients) and AR group (74 patients). In the VR group, each subject underwent a 20-min short-term plastic visual perceptual training based on a VR platform, and in the AR group, based on an AR platform. The best-corrected visual acuity (BCVA), fine stereopsis, and contrast sensitivity function (CSF) were measured before and after training. Results. The BCVA (P < 0.001) and fine stereopsis (P < 0.05) were improved significantly both in VR and AR group after training. Moreover, in the AR group, the CSF showed the value of all spatial frequencies had a statistically signiﬁcant improvement after training (P < 0.05), while in the VR group, only the value of spatial frequency 12 improved significantly (P = 0.008). Conclusions. This study showed that the short-term plastic visual perceptual training based on VR and AR technology can improve BCVA, fine stereopsis and CSF of refractive amblyopia. It was suggested that the visual perceptual training based on the VR and AR platforms may be potentially applied in treatment for amblyopia and provided a high-immersing alternative.